Pembenahan Keuangan Masjid Ashriyah Nagari Saok Laweh Kabupaten Solok, Sumatera Barat - Rayna Kartika; Rinaldi Munaf; Annisaa Rahman; Atika Gando Suri (Warta Pengabdian Andalas, 2021)
A mosque is a Muslim centre to be held in high esteem and maintained. That management would include physical or nonphysical enhancement, increased worship function, and others. Functionally, a mosque needs to be run as well as possible, so good mosque management is required. Therefore, every mosque's management should have transparency regarding financial transactions. As a form of a nonprofit public sector organization, a mosque must create a financial report consistent with a definitive statement of financial accounting (PSAK) 45 that regulates nonprofit reporting. The objective of the public's service was to provide allocated financial statements to the Ashriyah Saok Laweh using the Excel app-based program (Akoontan). This provision is necessary for the administrator of Ashriyah Saok Laweh to be able to comprise the financial report and present the easily understood finance report of the donor and the worshiper mosque Ashriyah Saok Laweh, distric of Solok, West Sumatra.